Seams to postpone the end of the world: reflections on the work A vida não é útil, by Aílton Krenak - Nogueira, Bernardo Gomes Barbosa (2023)
The text intended to present the thoughts of Aílton Krenak on his work “A vida não é útil” and make it dialogue with contemporary interdisciplinary reflections, in forms of seams supported by a critical epistemology and that point out textures and other ways of inhabiting, beyond the neoliberal trap, in search of ideas that postpone the end of the world. The author comes to the conclusion that his people are in the midst of disaster and that it would make no sense to stop living the experience. At the same time, in a courageous and existentialist way, he will exult us to reflection, by bringing the allegory of a desert, which he encourages us, without hesitation, to cross.